Moral exemplarism and atonement - Crisp, Oliver (Scottish journal of theology, 2020)
In recent work on the doctrine of atonement there has been little positive said about the view that Christ's work is principally a moral example. This article addresses that lacuna. It sets out two versions of the moral example doctrine, which are often conflated in the literature. According to the first, Christ is merely a moral example. Such a view does not amount to a doctrine of atonement. According to the second, Christ's moral example brings about reconciliation with God through a transformative experience. This does amount to a doctrine of atonement. I raise some traditional objections to the moral example view and show that it has resources with which to withstand them. However, moral exemplarism still has difficulties dealing with a cluster of biblical motifs about atonement. In the final analysis, it is a partial but not complete account of the saving work of Christ.